SOCIAL SKILLS OF THE BASIC EDUCATION TEACHER FACING AFFECTIVITY AND SUBJECTIVITY - Deivisom da Silva Rozado, Daniel (Revista Gênero e Interdisciplinaridade, 2021)
Important changes occurred in the training of teachers in the national scenario have raised the importance of working on the social skills of teachers, with a view to a more general training in the field of education. In this context, social skills play an important role, as they are a set of behaviors emitted by a person in an interpersonal context that expresses feelings, attitudes, desires, opinions or rights in a way that is appropriate to the situation, respecting others; thus contributing to job satisfaction and a good quality of life. This article aimed to study the social skills of teachers in basic education in the face of affectivity and subjectivity through a literature review of the literature. For this purpose, research on theoretical references already analyzed, and published by written and electronic means, such as books, scientific articles, pages of web sites in the area, was used as an investigation strategy. It results from this understanding that social skills and subjective well-being are a transforming and facilitating phenomenon in the process of learning and teacher training. It is concluded that these studied constructs are of great relevance for education, especially for the mental health of the subjects involved